2016
DOI: 10.1111/dmcn.13109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parent‐delivered action observation therapy on upper limb function in unilateral cerebral palsy: a randomized controlled trial

Abstract: Aim To determine whether home‐based, parent‐delivered therapy comprising action observation (AO) and repeated practice (RP) improves upper limb function more than RP alone in children with unilateral cerebral palsy (UCP). Method Design: single‐blinded parallel‐group randomized controlled trial with 1:1 allocation comparing AO+RP (intervention) with RP alone (control). Randomization: computer‐generated, with allocation concealment by opaque sequentially‐numbered envelopes. Setting: northern England, August 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
76
2
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(112 citation statements)
references
References 31 publications
1
76
2
22
Order By: Relevance
“…For preschool and primary school age children with unilateral CP, parent‐delivered therapy was shown to lead to improvements in upper limb function (Ferre et al, ; Kirkpatrick, Pearse, James, & Basu, ). Such programmes require intensive parental support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For preschool and primary school age children with unilateral CP, parent‐delivered therapy was shown to lead to improvements in upper limb function (Ferre et al, ; Kirkpatrick, Pearse, James, & Basu, ). Such programmes require intensive parental support.…”
Section: Introductionmentioning
confidence: 99%
“…Such programmes require intensive parental support. As an example (Kirkpatrick et al, ), parents of 70 children aged 3–10 years with unilateral CP were supported in providing home‐based activities, personalized to the child's own interests, abilities, and level of hand function. Support included training, provision of written instructions, home visits, and regular telephone contact, plus contact for troubleshooting.…”
Section: Introductionmentioning
confidence: 99%
“…They used the measure with an exclusively unilateral spastic cerebral palsy (USCP) cohort, as did we in an earlier paper. 3 The questionnaire is validated for children with all types of CP between the ages of 6 years and 15 years, and when used exclusively with children with USCP the item hierarchies may be altered. 4 While item hierarchy was found to be invariant across CP subtypes in the study, 1 British and American versions of the questionnaire have not been Rasch analysed following translation from the original French.…”
mentioning
confidence: 99%
“…There is increasing evidence for the efficacy of this method in adults with hemiplegia during the subacute and chronic phases of stroke. 2 In their trial, which addresses the efficacy of action observation therapy in children with unilateral cerebral palsy (CP), Kirkpatrick et al 3 demonstrate that there is no added-value of action observation over repetitive motor training, in a home-based, parent-delivered variant of the approach. This contrasts with a previous randomized trial in children with unilateral CP by Sgandurra et al, 4 which had shown significant improvements in bimanual function following more intensive, therapist-delivered, action observation therapy.…”
mentioning
confidence: 99%
“…It also reduces nutrient intakes in a group with already severe nutritional issues. 3 Singular diseases such as ataxia telangiectasia should not be judged by the same standards as more common events. The strengths of this study include the absence of invasive techniques, which in this group is preferred in terms of gaining agreement and compliance (even though invasive techniques might be preferred in other groups).…”
mentioning
confidence: 99%